Patient with Hemiparkinsonism Secondary to a Gun Pellet in the Contralateral Substantia Nigra. Issue 1 (7th December 2017) - Shalash, Ali; Abushady, Eman; Hamid, Eman; Salama, Mohamed; Ibrahim, Yosra Abdelzaher
Abstract: View Supplementary Video 1 A 33 year‐old male presented with right upper limb rest tremor that disappeared on action, posture associated with bradykinesia, and rigidity of right upper and lower limbs (VideoS1 ). Patient also presented right‐sided pyramidal weakness (grade 4), hyperreflexia, extensor plantar response, and hemihypesthesia. Skull X‐ray and computed tomography (CT) of the brain showed several metal pellets producing multiple artifacts (Fig.1 A, B). Only one pellet settled in brain parenchyma (left midbrain), while other pellets settled in the skull bone (Fig.1 A). Transcranial sonography (TCS) was performed, confirming that the midbrain pellet was placed within the left substantia nigra (Fig.1 C). Levodopa challenge test was conducted, showing no improvement (pre‐ and post‐l‐dopa motor UPDRS were 21 and 20, respectively). A further chronic trial of l‐dopa (for 3 months) also proved negative. Biperiden and propranolol were also tried with negative results. Hemiparkinsonism has been previously reported secondary to midbrain lesions.1 2 To the best of our knowledge, movement disorders (secondary to brain injuries) related to bullet fragments have been scantly reported. In one reported case, hemiparkinsonism and dystonia were the result of a bullet in midbrain, 2 and in another, dystonia was caused by a bullet in internal capsule.3 Abstract : View Supplementary Video 1